2017
DOI: 10.1016/j.ijscr.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

A variation of Musculocutaneous nerve without piercing the coracobrachialis muscle while communicating to the median nerve: A case report and literature review

Abstract: HighlightsThe Musculocutaneous nerve is one of the terminal branches of the lateral cord (C5– C7) in the axilla that runs downwards by piercing the coracobrachialis muscle, then enters to anterior compartment of the arm.The Median nerve is one of the three major nerves of the forearm and hand which is derived from the medial and lateral cords of the brachial plexus in the axillary region that has not any branch in the arm exceptionally in some cases may has a communication branch with the Musculocutaneous nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…It was reported that the brachial plexus is a variative part of the peripheral nerve system. The musculocutaneous nerve variations, which have an incidence of 6.25% according to the literature, are mainly divided into two groups: Its absence and the presence of a communication between the musculocutaneous and median nerves [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that the brachial plexus is a variative part of the peripheral nerve system. The musculocutaneous nerve variations, which have an incidence of 6.25% according to the literature, are mainly divided into two groups: Its absence and the presence of a communication between the musculocutaneous and median nerves [3].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these and similar neural and vascular variations is important in respect of the possible nerve injuries, which may be caused by a piercing or cutting trauma in the upper extremity. coracobrachialis muscle and ends in the sensorial branch or in the lateral side of the forearm after innervating these three muscles [3].…”
Section: Bilateral Variations Of Median Nerve Formation and Endpoint mentioning
confidence: 99%
See 3 more Smart Citations